2019
DOI: 10.1016/j.ebiom.2019.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic augmentation of the hypercholinergic endophenotype in DYT1 knock-in mice induced erratic hyperactive movements but not dystonia

Abstract: Background The most prevalent inherited form of generalized dystonia is caused by a mutation in torsinA (DYT1, ∆GAG) with incomplete penetrance. Rodent models with mutated torsinA do not develop dystonic symptoms, but previous ex vivo studies indicated abnormal excitation of cholinergic interneurons (ChI) and increased striatal acetylcholine. Methods We used in vivo optogenetics to exacerbate this endophenotype in order to determine its capacity to trigger dystonic symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 57 publications
1
26
1
Order By: Relevance
“…TorsinB overexpression did not change cortical thickness, striatal volume, striatal Nissl+ small and medium cell number, or striatal GFAP immunoreactivity in Dlx-CKO and Cre control mice ( Figure S6A-D). TorsinB overexpression completely prevented the loss of dorsal striatal ChIs that have been linked to motor and electrophysiologic abnormalities in dystonia mouse models [23,[29][30][31][32][33][34]. Analysis using unbiased stereology demonstrated that Dlx-CKO mice had 33.5% fewer ChIs compared to Cre controls, whereas the B-OE allele completely prevented this loss ( Figure 4C-D).…”
Section: Torsinb Overexpression Prevents Chi Degeneration and Dystonimentioning
confidence: 94%
“…TorsinB overexpression did not change cortical thickness, striatal volume, striatal Nissl+ small and medium cell number, or striatal GFAP immunoreactivity in Dlx-CKO and Cre control mice ( Figure S6A-D). TorsinB overexpression completely prevented the loss of dorsal striatal ChIs that have been linked to motor and electrophysiologic abnormalities in dystonia mouse models [23,[29][30][31][32][33][34]. Analysis using unbiased stereology demonstrated that Dlx-CKO mice had 33.5% fewer ChIs compared to Cre controls, whereas the B-OE allele completely prevented this loss ( Figure 4C-D).…”
Section: Torsinb Overexpression Prevents Chi Degeneration and Dystonimentioning
confidence: 94%
“…In DYT1 knock-in (KI) mice, which do not develop dystonic symptoms like other viable DYT1 models [4], extracellular acetylcholine was found to be increased in the striatum and blocking of acetylcholine receptors normalized D2 receptor mediated effects on striatal ChI [5]. In addition to these interesting findings, our data on in vivo optogenetic stimulations of striatal ChI supported an endophenotype of dysregulated cholinergic activity, although depolarizing of these interneurons was not sufficient to induce overt dystonia in DYT1 KI mice [6].…”
Section: Introductionmentioning
confidence: 54%
“…They were bred and housed in the institute’s facility in groups up to 6 littermates. Genotypes were assessed by polymerase chain reaction (PCR) amplification analysis of DNA extracted from ear tissue using PuReTaq Ready-To-Go Beads (GE Healthcare) as described previously [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, the microdialysis guide cannula was stereotactically implanted into the right murine striatum under 2.0% isoflurane anesthesia (CP-Pharma, Burgdorf, Germany) and 0.1% bupivacaine (Jenapharm, Jena, Germany) using the following coordinates in millimeter distance to the bregma and the skull surface according to the atlas of Franklin and Paxinos [17] in a stereotaxic frame (Stoelting, Wood Dale, IL, USA): anterioposterior + 0.8, mediolateral − 1.9, and dorsoventral 2.6. These coordinates were comparable to those used for previous experiments in mice [18]. The cannula was held in place with additional anchor screws and dental acrylic cement (Paladur ® , Heraeus Kulzer, Germany) on the skull surface.…”
Section: Animalsmentioning
confidence: 82%